“Everything is related”. Dialogue, network communication, and integral ecology - Carbajo Núñez, Martín (Revista Eclesiástica Brasileira, 2020)
In the light of the Catholic Magisterium and the Franciscan intellectual tradition, this paper asserts that interaction and communication are constitutive aspects of all that exists. “Everything is related.” In this holistic perspective, “truth is lógos which creates diá-logos, and hence communication and communion” (CV 4). Being in relationship is not an option, but an intrinsic requirement for ourselves and for all creatures. Many scientific data prove that, in the entire ecosystem, collaboration prevails over conflict. We also share with many living beings the same physical-chemical substrate and “a good part of our genetic code” (138). Therefore, we must strengthen the “awareness of our common origin, of our mutual belonging, and of a future to be shared with everyone” (202). Social media should reinforce this web of life, promoting dialogue and communication at all levels. Keywords: Dialogue; Communication; Integral ecology; Internet; Digital era. À luz do Magistério católico e da Tradição intelectual franciscana, este artigo afirma que a interação e a comunicação são aspectos constitutivos da realidade. “Tudo está relacionado”. Nesta perspectiva holística, “a verdade é ‘lógos’ que cria ‘diá-logos’ e, portanto, comunicação e comunhão” (CV 4). Relacionar-se não é uma opção, mas uma exigência intrínseca, tanto para nós como para as demais criaturas. Muitos dados científicos demonstram que, no ecosistema como um todo, a colaboração é mais decisiva do que o conflito. Partilhamos com muitos seres vivos o mesmo substrato físico-químico e “boa parte de nossa informação genética” (138). Portanto, devemos fortalecer “a conciência de uma origem comum, de uma mútua pertença e de um futuro compartilhado por todos” (202). As redes sociais e os meios de comunicação social devem reforçar esta rede da vida, promovendo o diálogo e a comunicação em todos os níveis.